Integrative assessment of organotin contamination in a southern European estuarine system (Ria de Aveiro, NW Portugal): Tracking temporal trends in order to evaluate the effectiveness of the EU ban - Sousa, A.
Organotin (OT) compounds have been used as biocide agents in antifouling paints since the mid 1960s and are now ubiquitous in the marine environment. Due to their high toxicity to non-target species they were banned from antifouling paints in the European Union in 2003 (2002/62/EC directive). The aim of the present work is to assess any obvious decline of the OT environmental levels at Ria de Aveiro (NW Portugal) after the ban. The organotins – monobutyltin (MBT), dibutyltin (DBT), tributyltin (TBT), monophenyltin (MPT), diphenyltin (DPT), triphenyltin (TPT), monoctyltin (MOT), dioctyltin (DOT) and trioctyltin (TOT) – were quantified in the gastropod Nassarius reticulatus , in the mussel Mytilus galloprovincialis and in sediments. Imposex (imposition of male characters on females of gonochorist gastropods) in N. reticulatus was additionally used as a biomarker of TBT pollution. Time comparisons show a slight decrease of imposex between 2003 and 2005 probably as a consequence of the EU ban, though in some cases this trend seems to have started earlier since 2000. The fraction of TBT relatively to its metabolites has been decreasing over the last years but still remains high suggesting that there are still recent inputs of this compound into the study area.